(untitled) (Journal of the College of Basic Education, 2024)
The aim of the current research is to identify 1 Psychological presence among kindergarten children. She contributed to the search for kindergarten teachers in the districts of Baghdad, Al-Karkh 1, Al-Karkh 2, and Al-Karkh 3. When the goal of the research was not achieved, the first researcher, Datan, used the professional identity scale, which the researcher carried out the work of adopting a scale (Mazouzi, 2020), which is based on Osti’s definition and includes the scale (30).) A sub-paragraph on four members (sense of recognition, sense of independence, belonging, effectiveness) As for the psychological presence scale, the researcher adopted the scale (Muhammad, 2021), which was based on Rife’s definition. The scale in its final form consists of (33) items distributed over five areas: (self-acceptance, independence, positive relationships with others, personal growth, purpose in life). Validity and reliability were verified, and reliability of professional identity and psychological presence was extracted using the test-retest method and the Cronbach equation. The researcher came up with the following seven Characteristics of children’s sports are psychological presence Because of professional identity in psychological existence Through the results, the researcher came up with some suggestions: such as comparing government and private kindergarten teachers. Conducting a study to determine the extent to which professional identity contributes to the professional performance of kindergarten teachers. Conducting a study entitled a proposed program to achieve the